2021
DOI: 10.3233/jad-210319
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and Parkinson’s Disease: Risk Factors for 30-Day Mortality in Nursing Home Residents with COVID-19

Abstract: Background: The COVID-19 pandemic has led to high mortality rates in nursing homes (NHs) in Europe. For adequate risk management and good prognostications, it is essential to identify mortality risk factors. Objective: This study aimed to determine whether previously identified risk factors for 30-day mortality in Dutch NH residents with COVID-19 are unique to COVID-19. Methods: In this cohort study, we included 1,294 NH residents with COVID-19 (cases) and 17,999 NH residents without COVID-19 (controls, from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…The mortality rate was 26,9%, with a slight increase, not statistically significant ( p value 0,33), compared to the previous year (24,3%), and higher in female population. This is apparently in contrast with literature [ 13 16 ], where mortality is higher among men. But the majority of papers refer to acute or intensive care settings [ 17 , 18 ], while in our paper, we refer to a post-acute setting with a prevalence of female survived patients, burned with greater clinical impairment.…”
Section: Messagecontrasting
confidence: 98%
“…The mortality rate was 26,9%, with a slight increase, not statistically significant ( p value 0,33), compared to the previous year (24,3%), and higher in female population. This is apparently in contrast with literature [ 13 16 ], where mortality is higher among men. But the majority of papers refer to acute or intensive care settings [ 17 , 18 ], while in our paper, we refer to a post-acute setting with a prevalence of female survived patients, burned with greater clinical impairment.…”
Section: Messagecontrasting
confidence: 98%
“…A pooled analysis showed that PD was associated with poor in-hospital outcomes, including severe disease (odds ratio 2.61, 95% CI 1.98–3.43) and mortality from COVID-19 (odds ratio 2.63, 95% CI 1.50–4.60), and the risk increased with age [ 7 ]. Furthermore, among Dutch nursing home residents affected by COVID-19, those with PD had a strongly increased risk of death compared to those without PD [ 8 ]. People with PD have also experienced indirect consequences of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that more than half of the respondents confirmed being afraid of infection. Fear may also be related to previous data concerning higher mortality rates in the PD population compared to the general population, especially in those who were older, with longer PD duration, hypertension or coexisting dementia [ 34 , 38 , 39 ]. However, other scientific studies showed that the risk of infection, severe disease or death among people with PD was comparable to that of the general population [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%